2022
DOI: 10.1590/1982-0224-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea dragonfishes (Teleostei: Stomiiformes) collected from off northeastern Brazil, with a review of the species reported from the Brazilian Exclusive Economic Zone

Abstract: The Stomiiformes includes about 455 species of mostly mesopelagic fishes in the families Diplophidae, Gonostomatidae, Phosichthyidae, Sternoptychidae, and Stomiidae. Here we report 55 species of the order collected during the ABRACOS (Acoustics along the BRAzilian COaSt) expeditions off northeastern Brazil, including islands and seamounts of Fernando de Noronha Ridge. Triplophos hemingi (Diplophidae), Pachystomias microdon and Melanostomias biseriatus (Stomiidae) are recorded for the first time in the western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…When all published accounts of the ABRACOS expeditions are considered together (Afonso et al, 2021;Eduardo et al, 2018Eduardo et al, , 2019Eduardo et al, , 2021Mincarone et al, 2019Mincarone et al, , 2020Mincarone et al, , 2021Villarins et al, 2022; this study), a total of 50 species of deep-sea fishes are newly reported for Brazilian waters. Some of those records are also new for the western South Atlantic or larger areas, as the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When all published accounts of the ABRACOS expeditions are considered together (Afonso et al, 2021;Eduardo et al, 2018Eduardo et al, , 2019Eduardo et al, , 2021Mincarone et al, 2019Mincarone et al, , 2020Mincarone et al, , 2021Villarins et al, 2022; this study), a total of 50 species of deep-sea fishes are newly reported for Brazilian waters. Some of those records are also new for the western South Atlantic or larger areas, as the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the team members of the Project ABRACOS (Acoustics along the BRAzilian COaSt) conducted a multidisciplinary study off north‐eastern Brazil to better understand the degree of connectivity between the continental margin and the oceanic islands and seamounts of the region. The two surveys performed along the study area revealed a rich mesopelagic fish fauna, including many new distributional records in groups of the Teleostei such as the Argentiniformes (Mincarone et al ., 2021), Stomiiformes (Eduardo et al ., 2020a, 2020b; Villarins et al ., 2022), Ceratioidei (Mincarone et al ., 2021), Stephanoberycoidei (Afonso et al ., 2021), Caristiidae (Mincarone et al ., 2019), Howellidae (Eduardo et al ., 2019) and Trichiuridae (Eduardo et al ., 2018). Here, we provide new distributional records of rare species of the families Alepocephalidae, Chiasmodontidae, Giganturidae, Neoscopelidae, Notosudidae, Scopelarchidae, Stylephoridae and Trachipteridae collected during the ABRACOS expeditions off north‐eastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclotone is another seemingly abundant genus of mesopelagic fish in the SWTA (Olivar et al, 2017). Eight species of the genus were reported for the SWTA: C. acclinidens, C. alba, C. braueri, C. microdon, C. obscura, C. pallida, C. parapallida, and C. pseudopallida (Villarins et al, 2022) The sampling gears employed in the study, however, seemed to be only partially adequate to collect specimens of the genus. In several trawls we observed onboard that a substantial number of specimens of Cyclothone escaped back into the sea during the hoisting of the net.…”
Section: Diversity and Distributionmentioning
confidence: 96%
“…Excluding a few specimens of the Stomiidae, Sternoptychidae, and Myctophidae used for biological analyses (Eduardo et al, 2020a;Eduardo et al, 2020b;Eduardo et al, 2021), all specimens were deposited in the NPM -Fish Collection of the "Instituto de Biodiversidade e Sustentabilidade, Universidade Federal do Rio de Janeiro" (NUPEM/UFRJ). Taxonomic classification follows Nelson et al (2016), with exceptions noted in Villarins et al (2022) for the Stomiiformes.…”
Section: Data and Specimen Collectionmentioning
confidence: 99%
See 1 more Smart Citation